A study on the production of tomato (Lycopersicon esculentum) paste from local varieties - Reyes, Ma. Stella C.; Sales, Alicia C. (1984.)
The possibility of processing local tomato varieties into tomato paste was studied. The local tomato, Lycopersicon esculentum variety Peto HB, which possessed a moisture content of 92.7% and a total solids content of 7.1% was determined to be the most suitable for tomato paste production as compared to Castle HY, Calypso and Indian River varieties. The finished product had a pH of 4.3, titratable acidity of 2.68%, Munsell value of 7.5R 3/10 which corresponds to a combination of red-brown colors, due to moderate heat damage, moisture content of 67%, total solids content of 32.8%, and a mold count of 0%. It was sensorially evaluated to have a bright red color, "medium but pasty" to "thick but pasty" consistency, characteristic tomato flavor, and a general acceptability of "like moderately" to "like very much." The tomato paste produced from the Peto HB variety was also determined to be significantly preferred than the comercially available tomato paste. The total cost of the tomato paste production was computed to be P59.01 per 100 grams of the product as of April, 1984.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Tomato products; Tomato sauces